‘From beyond the rivers of Cush’ : negotiating ethnic identity and Cushite-Israelite interrelations in the Hebrew Bible - Burrell, Kevin (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhD)--Stellenbosch University, 2018.